Microbial innovations in the world of food†. Issue 1 (2nd January 2017) - Kawasaki, Hisashi; Ueda, Kenji
Abstract : Technological developments in Japan based on the results of microbial research were a major pillar supporting the postwar industrial revolution. The wellspring of these advancements was the sophisticated technology used in traditional brewing, a foundation of the characteristic Japanese food culture. In this manuscript, we will describe the fermentative production of amino acids and nucleic acids following the discovery of the umami component so distinct in Japanese cuisine, which finally revealed the true power of microbial production. Thereafter, we will describe acetic acid production stemming from brewed vinegar production and the fermentative production of some other organic acids. Finally, we will delve into the massive scale of innovations achieved by the discovery of valuable micro-organisms and how they have affected the field of food.